2
$\begingroup$

I know that the property of duality says:

$$x(t) \iff X(f)$$ $$X(t) \iff x(-f) "="x(t=-f)$$

and I know that:

$$\delta(t-t_0) \iff exp(-j2\pi ft_0)$$

If I apply the duality property, I get:

$$exp(-j2\pi f_0t) \iff \delta(-f-f_0)$$ $$exp(j2\pi f_0t) \iff \delta(f-f_0)$$

instead the correct result is:

$$exp(j2\pi f_0t) \iff \delta(f+f_0)$$

Why?

Thank you for your help.

$\endgroup$
  • 2
    $\begingroup$ I guess $exp(j2\pi f_0t) \iff \delta(f-f_0)$ is correct, while $exp(j2\pi f_0t) \iff \delta(f+f_0)$ is false. $\endgroup$ – the_candyman Jul 1 '17 at 10:10
5
$\begingroup$

I think you're getting confused between $t$ and $f$ , Duality says

$$x(t) \Leftrightarrow X(\omega) \implies X(t)\Leftrightarrow2\pi x(-\omega) $$ Or in terms of $f$ $$x(t) \Leftrightarrow X(f) \implies X(t)\Leftrightarrow x(-f) $$

So for $\delta(t-t_0)$ $$\delta(t-t_0) \Leftrightarrow \mathrm{exp}(-jt_0 2\pi f) \implies \mathrm{exp}(-jt_02\pi t) \Leftrightarrow \delta(-f-t_{0})=\delta(f+t_0)$$ And for $\delta(t+t_0)$ $$\delta(t+t_0) \Leftrightarrow \mathrm{exp}(jt_0 2\pi f) \implies \mathrm{exp}(jt_02\pi t) \Leftrightarrow \delta(-f+t_{0})=\delta(f-t_0)$$ Note that $\delta(t)$ is even function

Please let me know if i can improve my answer somehow , thanks !

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.